Predation on the Kelaart's Pipistrelle Bat, Pipistrellus ceylonicus Kelaart (Chiroptera: Vespertilionidae), by the Reddish Parachute Tarantula, Poecilotheria rufilata Pocock (Araneae: Theraphosidae), in Chinnar Wildlife Sanctuary, Kerala, India - ANOOP DAS, KARUMAMPOYIL SAKTHIDAS; SREEKALA, LEELAMBIKA KRISHNAN; ABDURAHIMAN, OLAPILAN (Tropical Natural History, 2012)
-